What training do artists need to work in healthcare settings?. Issue 2 (30th November 2009) - Moss, H; O'Neill, D
Abstract : Given the increased attention paid to the development of arts in healthcare settings, the need for a formalised training framework to enable artists to work comfortably and safely in healthcare settings has become pressing. This paper sets out a review of literature and best practice regarding the training of professional artists wishing to work in healthcare settings. The authors' research confirms the gap in the arts sector with regard to such training. Very little formal training is currently available internationally for artists wishing to work in healthcare settings outside of the arts therapies professions. There is a need for the health sector to formalise a currently ad hoc approach to employing artists in healthcare settings. There are a number of best-practice models of arts and health practice from which we can learn but relatively scant literature on course development. The arts therapies are relatively expert in the domain of using the arts in healthcare and while there are different aims and intentions to this work, it is important that any establishment of arts and health training recognises the contribution and expertise of arts therapists in the healthcare arena. A culture of mutual learning between the arts therapies and the arts and health specialists is recommended.